Analisis Tingkat Kepercayaan Nasabah pada Bank Syariah Indonesia dan Bank Rakyat Indonesia di Sungai Penuh - Nurafni Okta Safitri; Zull ihsan mu’arrif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Indonesian people's bank (BRI) and Indonesian sharia bank (BSI), both have different implementations. Indonesian people's banks operate based on conventional financial principles which generally use interest as the main mechanism for making profits. However, in achieving this, many factors influence it, starting from customer trust in Bsi and Bri banks, so the aim of this research is to find out the level of customer trust in sharia banks. This research uses a qualitative approach with descriptive research type. This method was chosen to gain an in-depth understanding of the factors that influence customer trust in BSI and BRI in Sungai Banyak City. The research data consists of primary data, which is obtained directly through in-depth interviews with customers. The results of this research are that customer trust is formed from how the service is performed, from communication to behavior control, because it is a key or factor in customer trust.